انعكاسات البيئة الرقمية على العاملين باذاعة الجزائر - حليمة احسان حسان; نزيهة دصعة (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة: جاءت دراستنا بعنوان انعكاسات البيئة الرقمية على العاملين بإذاعة الجزائر وانطلقت دراستنا من الإشكالية: كيف تنعكس البيئة الرقمية على أداء العالمين بإذاعة الجزائر من الأغواط؟ وللوصول الى إجابة افترضنا عدة فرضيات وهي:  تنعكس البيئة الرقمية إيجابيا على العالمين بإذاعة الأغواط.  تنعكس البيئة الرقمية سلبا على العاملين بإذاعة الأغواط.  مستقبل الصحافة في الجزائر يعتمد على قدراتها في التكيف مع التطورات المتسارعة في مجال التكنولوجيا الرقمي. كما نهدف من خلال دراستنا الى التعرف على انعكاسات البيئة الرقمية على أداء العالمين بإذاعة الجزائر من الأغواط، وفي دراستنا اعتمدنا على المنهج الوصفي وأداة جمع البيانات تمثلت في الاستبيان لدراسة مجتمع الدراسة المتكون من 20عاملا بالمؤسسة إذاعة الاغواط حيث توصلنا الى النتائج التالية: 1. الإذاعة المحلية بالأغواط تستخدم البث الرقمي في نقل وعرض برامجها الاذاعية لان البث الرقمي يممتاز بالسرعة والسهولة والدقة والامانفي نقل الاخبار والمعلومات. 2. للرقمة تأثيرات إيجابية عن الإذاعة المحلية منها التوسع في القاعدة الجماهرية وتحقيق من صحة الاخبار والنجاعة في معالجتها، وسهولة الحصول على المعلومات والمادة الإخبارية وتطوير العملية الاتصالية بالمؤسسة بتسريعها وتكثيفها والتطوير من وسائلها، كما ان لها سلبيات منها التواكل الاتكاء وغياب عنصر الدقة والتأكد من المادة الإخبارية كما ان من سلبياتها السرقة الإعلامية. 3. شهدتالإذاعةتحولاتجذريةفيطريقةعملهاوتقديممحتواها حيث انتقلتالعديدمنمحطاتالإذاعةإلىالبثالرقميعاليالجودة،مماأتاحتقديممحتوىأفضلوأكثروضوحًاللمستمعين عبر وسائل مختلفة البثعبرالإنترنت: يمكنالآنللمحطاتالإذاعيةالبثعبرالإنترنت،ممايسمحللمستمعينبالاستماعإلىالبرامجمنأيمكانفيالعالمباستخدامأجهزةمتصلةبالإنترنت. وسمحتالتكنولوجياالرقميةللإذاعةبالتفاعلبشكلأكبرمعالجمهورمنخلالوسائلالتواصلالاجتماعيوالبريدالإلكترونيوالرسائلالنصية. Study summary Our study was entitled: The repercussions of the digital environment on employees of Radio Algeria Our study started from the problem: How does the digital environment reflect on the performance of the two scholars on Radio Algeria from Laghouat? To arrive at an answer, we assumed several hypotheses:  The digital environment reflects positively on the people of Radio Laghouat.  The digital environment reflects negatively on the employees of Radio Laghouat.  The future of journalism in Algeria depends on its ability to adapt to the rapid developments in the field of digital technology. Through our study, we also aim to identify the repercussions of the digital environment on the performance of the scientists at Radio Algeria from Laghouat. In our study, we relied on the descriptive approach and the data collection tool represented by the questionnaire to study the study population consisting of 20 workers at the Radio Laghouat Foundation, where we reached the following results: 1. Local radio in Laghouat uses digital broadcasting to transmit and display its radio programs because digital broadcasting is characterized by speed, ease, accuracy, and safety in transmitting news and information. 2. La numérisation a des effets positifs sur la radio locale, notamment en élargissant l'audience, en vérifiant l'exactitude des informations et l'efficacité de leur traitement, en facilitant l'obtention d'informations et de matériel d'information, et en développant le processus de communication de l'organisation en l'accélérant et en l'intensifiant et en développant ses moyens. Il présente également des inconvénients, notamment la dépendance, le manque d'exactitude et de vérification du matériel. L'un de sesinconvénients est le vol de médias. 3. Radio has witnessed radical transformations in the way it operates and delivers its content as many radio stations have moved to high-quality digital broadcasting, which has made it possible to provide better and clearer content to listeners through various means. Online broadcasting: Radio stations can now broadcast over the Internet, allowing listeners to listen To programs from anywhere in the world using devices connected to the Internet. Digital technology has allowed radio to interact more with the audience through social media, email and text messages.
اذاعة الاغواط نموذجا